Information visualisation : from theory, to research, to practice - Lonsdale, Maria dos Santos (London : SAGE Publications Ltd., 2023)
"In a world of information overload, this book will help you to cut through the noise and communicate information with clear, efficient, and engaging visualisations. Taking you on a journey through a full range of different types of visualisations including infographics and motion graphics, the book: Explains the underlying principles behind information visualisation, including the science of visual perception and cognition Provides easy-to-digest guidelines that bring research and best practice together Showcases a range of real-world applied examples, and outlines the do's and don'ts of different approaches Shows how to use research methods to design with and for your target audience. From an expert with years of experience researching, teaching, and doing information visualisation, learn how to make better and informed decisions around visualisation design that are appropriate for both your data and audience"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Information visualization; Visual analytics